Introduction to the Ekedahl Invariants - Martino, Ivan (MATHEMATICA SCANDINAVICA, 2017)
In 2009, T. Ekedahl introduced certain cohomological invariants for finite groups. In this work we present these invariants and we give an equivalent definition that does not involve the notion of algebraic stacks. Moreover we show certain properties for the class of the classifying stack of a finite group in the Kontsevich value ring.